Data on monogenean (Platyhelminth) parasites in 11 populations of Astyanax aeneus (Pisces: Teleostei) in a neotropical river in Chiapas, south Mexico - Salgado Maldonado, Guillermo; Mendoza Franco, Edgar F.; Caspeta Mandujano, Juan Manuel; Ramírez Martínez, Carlos (Elsevier, 2019)
The data presented in this article are related to the research article entitled “Aggregation and negative interactions in low-diversity and unsaturated monogenean (Platyhelminthes) communities in Astyanax aeneus (Teleostei) populations in a neotropical river of Mexico” publicated in Int. J. Parasitol. Parasites Wildl. 8 (2019) 203 e215. https://doi.org/10.1016/j.ijppaw.2019.02.005. This article describes the communities of monogenean parasites in 11 populations of a small characid freshwater fish Astyanax aeneus (Günther) separated by small geographical distances along 60 km of the Lacantún river in Chiapas, Mexico. We examined 15 A. aeneus from each of 11 locations (one sample in February, a second sample in August 2012), situated at the mouth of the streams opening into the main body of the Lacantún river, at the Montes Azules Biosphere Reserve in the Lacandon forest, Chiapas in southern Mexico. The area of study is located ~800 km from the mouth of the Usumacinta river in the Gulf of Mexico. In this paper we provide the data for 12 monogenean taxa. The material